Fragmented QRS (fQRS) in Acute Coronary Syndrome: Is It a More Potential Marker Than Predicted? - Ryan Ranitya (Interna Publishing, 2019)
Fragmented QRS (fQRS) complexes are electrocardiographic (ECG) findings which reflect impaired ventricular depolarization due to heterogeneous electrical activation of ischemic and or injured myocardium. Therefore, it had been associated with many cardiovascular diseases both ischemic and non-ischemic origin. To date, fQRS is considered a novel and convenient marker of myocardial scar or fibrosis. Thus, it has gained more interest to investigate the potential use of fQRS in cardiac disease, especially in acute coronary syndrome (ACS).